Motion Smoothness Metrics for Cannulation Skill Assessment: What Factors Matter? - Singh, Simar; Bible, Joe; Liu, Zhanhe; Zhang, Ziyang; Singapogu, Ravikiran (Frontiers in Robotics and AI, 2021)
Medical training simulators have the potential to provide remote and automated assessment of skill vital for medical training. Consequently, there is a need to develop "smart" training devices with robust metrics that can quantify clinical skills for effective training and self-assessment. Recently, metrics that quantify motion smoothness like Log Dimensionless Jerk (LDLJ